K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

Bài làm

G = 2x- 3x + 1

G = 2x2 - 2x - x + 1

G = -( 2x2 + 2x ) - ( x + 1 )

G = -2x( x + 1 ) - ( x + 1 )

G = ( x + 1 )( -2x - 1 )

# Học tốt #

Bài làm

H = -x2 + 5x - 4

H = -x2 + 4x + x - 4

H = -( x2 - 4x ) + ( x - 4 )

H = -x( x - 4 ) + ( x + 4 )

H = ( x - 4 )( -x + 1 )

# Học tốt #

27 tháng 9 2019

\(G=2x^2-3x+1=2x^2-2x-x+1\)

\(=2x\left(x-1\right)-\left(x-1\right)=\left(2x-1\right)\left(x-1\right)\)

\(H=-x^2+5x-4=-x^2+4x+x-4\)

\(=-x\left(x-4\right)+\left(x-4\right)=\left(1-x\right)\left(x-4\right)\)

\(I=x^2+4x+3=x^2+3x+x+3\)

\(=x\left(x+3\right)+\left(x+3\right)=\left(x+1\right)\left(x+3\right)\)

\(K=2x^2+7x+5=2x^2+2x+5x+5\)

\(=2x\left(x+1\right)+5\left(x+1\right)=\left(2x+5\right)\left(x+1\right)\)

\(L=-3x^2-5x-2=-3x^2-3x-2x-2\)

\(=-3x\left(x+1\right)-2\left(x+1\right)=\left(-3x-2\right)\left(x+1\right)\)

27 tháng 9 2019

G = 2x2 - 3x +1 =  2x2 -2x -x +1 =(x-1).(2x-1)

H = -x2 + 5x - 4 = -x2 + 4x +x-4 = (x-4).(1-x)

I = x2 + 4x + 3 = x2 + 3x + x + 3 =(x+3).(x+1)

K = 2x2 + 7x + 5 = 2x2 + 2x + 5x + 5 = (x+1).(2x+5)

L = -3x2 -5x -2 = -3x2 - 3x - 2x - 2 = -3.x(x+1) - 2.(x+1) = (x+1).(-3x-2)

14 tháng 12 2020

6x^2-(x-3)(3x+2)-6

=6x^2-6x^2+x-9x-6-6

=-5x-12

14 tháng 12 2020

undefined

18 tháng 12 2023

<=>55 - 3x = 25

<=>-3x = 25 - 55
<=>-3x = -30
<=>x=10

18 tháng 12 2023

55 - 3x = (-5)2

55 - 3x = 25

3x = 55 - 25

3x = 30

x = 30 : 3

x = 10

Vậy x = 10

19 tháng 9 2016

a) Ta co :

\(2^{30}=\left(2^3\right)^{10}=8^{10}\)

\(3^{20}=\left(3^2\right)^{10}=9^{10}\)

Vì \(8^{10}< 9^{10}\)

\(\Rightarrow2^{30}< 3^{20}\)

b)

Ta có :

\(7^6+7^5-7^4\)

\(=7^4\left(7^2+7-1\right)\)

\(=7^4.55\)

=> đpcm

19 tháng 9 2016

a)Ta có:

230 = (23)10 = 810

320 = ( 3)10 = 910

Vì 810 < 910 => 230 < 320

b) 7+ 7- 74

= 74 (72 + 7 - 1 ) 

= 74 *55 chia hết 55

Đpcm